Drug Focus: Pharmacogenetic studies related to cyclophosphamide-based therapy. (December 2009) - Pinto, Navin; Ludeman, Susan M; Dolan, M Eileen
Cyclophosphamide is a cornerstone in the treatment of many pediatric and adult malignancies, as well as in the treatment of refractory autoimmune conditions. Genetic factors are thought to play a role in the interindividual variation in both response and toxicities associated with cyclophosphamide-based therapies. This drug focus reviews the most compelling studies conducted on the pharmacogenetics of cyclophosphamide-based therapies. Broader pharmacogenomic studies are needed and may reveal additional factors important in susceptibility to toxicity and/or response to therapy.